2016
DOI: 10.1007/s10639-015-9456-7
|View full text |Cite
|
Sign up to set email alerts
|

Digital competences and long-term ICT integration in school culture: The perspective of elementary school leaders

Abstract: This study examines how the leaders of technology integration in educational institutions -school principals and ICT facilitators -assess systemic changes that occurred in their schools. The study collected the data from Israeli elementary schools towards the end of the third and the fourth years of the gradual National ICT program. The research questions explored (1) the predictors of the general school ICT culture and (2) changes over time in the general school ICT culture and its components. An online quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
86
0
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 48 publications
4
86
0
25
Order By: Relevance
“…From the analysis, it can be concluded that there seems to be an agreement that teachers' digital competence is important for uptake and use of digital technologies in teaching and learning practices. The first inductive sub-theme from the analysis concerns the impact of teachers' digital competence when it comes to ICT integration and pedagogical use of digital technologies (Blau and Shamir-Inbal 2017;Hatlevik 2016;Sipilä 2014;Wastiau et al 2013). Blau and Shamir-Inbal (2017) examined (from a school leader perspective) teachers' digital competences as one important component for ICT integration and pedagogical changes.…”
Section: Teachers and Their Teaching Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis, it can be concluded that there seems to be an agreement that teachers' digital competence is important for uptake and use of digital technologies in teaching and learning practices. The first inductive sub-theme from the analysis concerns the impact of teachers' digital competence when it comes to ICT integration and pedagogical use of digital technologies (Blau and Shamir-Inbal 2017;Hatlevik 2016;Sipilä 2014;Wastiau et al 2013). Blau and Shamir-Inbal (2017) examined (from a school leader perspective) teachers' digital competences as one important component for ICT integration and pedagogical changes.…”
Section: Teachers and Their Teaching Practicesmentioning
confidence: 99%
“…The first inductive sub-theme from the analysis concerns the impact of teachers' digital competence when it comes to ICT integration and pedagogical use of digital technologies (Blau and Shamir-Inbal 2017;Hatlevik 2016;Sipilä 2014;Wastiau et al 2013). Blau and Shamir-Inbal (2017) examined (from a school leader perspective) teachers' digital competences as one important component for ICT integration and pedagogical changes. In their study, they found that ICT integration and digital competence evolves over time and that digital competences must become an integral part of teachers' core teaching competences and not as something that is 'an add-on'.…”
Section: Teachers and Their Teaching Practicesmentioning
confidence: 99%
“…In particular, current school teachers still feel burdened in teaching effectively in the smart learning environment and supporting the skills learners expect to use in the future. Previous studies commonly supported the idea that if teachers could have a positive self-efficacy in ICT teaching and learning, they would be likely to easily adopt ICT instructions in classrooms (Blau and Shamir-inbal 2017;Chang et al 2017;Cheok and Wong 2015;Hatlevik 2017;Holden and Rada 2011;Teeroovengadum et al 2017;Willis et al 2018). Moreover, Reksten (2000) explained the importance of teachers' perceptions as follows: "The critical prerequisite for successful technology integration is preparing your staff and your school community to take on the positive aspects of an inviting school 'context' for technology change" (p. 9).…”
Section: Literature Reviewmentioning
confidence: 96%
“…In general, many governments in different countries have made considerable investments to equip schools with technology; however, fiscal and material resources do not always result in the successful implementation of technology-enriched learning in the classroom. Previous studies on smart learning have viewed teachers as a critical factor in successful implementation of smart learning in schools (Blau and Shamir-inbal 2017;Brinkley et al 2011;Teeroovengadum et al 2017;Willis et al 2018). Palfrey and Gasser (2008) described teachers and students as two very different generations.…”
mentioning
confidence: 99%
“…Moreover, creative computing is an important design activity which gives youth a real opportunity to 'learn by design' and to build important 21 st century digital literacy competences within the context of a complex design project (Blau & Shamir-Inbal, 2016;Brennan & Resnick, 2012). Instead of technical details of computation, creative computing emphasizes the interests of youth, their vivid imagination, and the realization of their creative potential (Benolol & Blau, 2016;Kafai, 2016).…”
Section: Framework and Literature Reviewmentioning
confidence: 99%